Scanogram for Sagittal Imbalance of the Spine: Low Dose Alternative for a Safer Diagnosis - M. Weisz, George; Albury, WR; D. Houang, M.; Matucci-Cerinic, Marco (Current Rheumatology Reviews, 2014)
The diagnosis of Fixed Sagittal Imbalance (FSI), previously known as Flat Back Syndrome, requires the measurement of spinal curvatures on a lateral radiograph in the standing position (C7-S1). It can be difficult to position a spastic patient, sometimes repeated exposure are required, at separate thoracic and lumbar levels, increasing the radiation dosage. CT Scanography is suggested as an alternative radiological diagnostic method since it is rapid to perform. The patient is comfortably positioned (horizontal) and it combines both prone and supine positions, therefore acting as a functional examination. This test was performed on 34 consecutive patients with fractured vertebrae (lumbar, dorsal) and with back pain persisting beyond the bone healing period. The functional scanogram was found to be accurate in diagnosing sagittal imbalances, but more importantly it offered reduction in radiation: in Entrance dose; in Effective dose and Absorption dose. Scanogram is therefore proposed as an alternative method for the diagnosis of FSI.
Keywords: sagittal imbalance